Sistem Keselamatan Terhadap Kebisingan Di Kamar Mesin Berbasis Mikrokontroler Arduino Uno - Ahmad Faqih Supriyadin; Edi Kurniawan; Eddi Eddi (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
One of the organs in the body that can help humans maintain balance is the ear. One of the body's main sound-producing organs is the ear, which also produces sound because it has unique receptors that can detect sound waves. However, the frequency range between 20 Hz and 20,000 Hz is the high limit that the ear can hear. This is why individuals often experience acute hearing loss after exposure to loud sounds or more than 20,000 Hz. A tool that can detect noise in an area, such as in an engine room, was created to overcome this problem, especially on ships After designing the tool and testing the safety system tool for noise in the engine room based on the Arduino Uno microcontroller, this system became a new technology for monitoring noise in the engine room. Then testing on all sensor readings worked well with an average percentage error on the ship running 0.70% and on the ship stopping 1.19% and the distance between the transmitter and receiver reaching a range of 290 cm without obstructions and with obstructions reaching around 130 cm. After all the equipment is working properly, earmuffs can be used to protect human hearing by educating all crew members to be able to use earmuffs when entering the engine room or going to work.